Dynamics of Ice Sheets and Glaciers - Greve, Ralf.; Blatter, Heinz; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
Dynamics of Ice Sheets and Glaciers presents an introduction to the dynamics and thermodynamics of flowing ice masses on Earth. Based on an outline of general continuum mechanics, the different initial-boundary-value problems for the flow of ice sheets, ice shelves, ice caps and glaciers are systematically derived. Special emphasis is put on developing hierarchies of approximations for the different systems, and suitable numerical solution techniques are discussed. A separate chapter is devoted to glacial isostasy. The book is appropriate for graduate courses in glaciology, cryospheric sciences, environmental sciences, geophysics and related fields. Standard undergraduate knowledge of mathematics (calculus, linear algebra) and physics (classical mechanics, thermodynamics) provide a sufficient background for successfully studying the text.
Ice in the Climate System -- Vectors, Tensors and Their Representation -- Elements of Continuum Mechanics -- Constitutive Equations for Polycrystalline Ice -- Large-Scale Dynamics of Ice Sheets -- Large-Scale Dynamics of Ice Shelves -- Dynamics of Glacier Flow -- Glacial Isostasy -- Advanced Topics -- Conclusions, Summary and Outlook -- Erratum.
Keywords: Physics; Earth sciences; Geophysics; Continuum physics; Fluids; Physics; Geophysics and Environmental Physics; Classical Continuum Physics; Geophysics/Geodesy.; Earth Sciences, general; Fluid- and Aerodynamics; Electronic books